UTILIZATION OF EDUCATION MANAGEMENT INFORMATION SYSTEM (EMIS) AND PRINCIPALS’ ADMINISTRATIVE EFFECTIVENESS IN SECONDARY SCHOOLS IN IKOM EDUCATION ZONE, CROSS RIVER STATE, NIGERIA. (Scientific Journal of Educational Management, Research and law, 2025)
At the secondary level of education, the administrative role of a principal is crucial in ensuring the uninterrupted operation of the entire school system. The adoption of a digitalized approach such as Management information system (MIS) becomes more necessary when all administrative efforts does not yield expected educational outcomes. Premised on this, a study on Utilization of Education Management Information System and Principals’ Administrative Effectiveness in Secondary Schools in Ikom Education Zone, Cross River State, Nigeria, was conducted.  The Education Zone was made up of 6 local government areas, namely; Abi, Boki, Etung, Obubra, Ikom and Yakurr. Correlational survey design was adopted. The study population comprised all the 112 principals in public secondary schools in Ikom Education Zone. There was no sampling as all the 112 principals were used for the study. An instrument titled “Education Management Information System and Principals’ Administrative Effectiveness Questionnaire (EMISPAEQ)” was used for data collection. It was structured on a four point rating scale of Strongly Agree (SA), Agree (A), Disagree (D) and Strongly Disagree (SD) weighted 4, 3, 2 and 1 respectively. Its validity was determined by three experts, two from the Department of Educational Management and one from the Department of Educational Foundations (Measurement and Evaluation Unit), faculty of Educational Foundations Studies, University of Calabar.  The Cronbach alpha was used to determine the reliability of the instrument which yielded the coefficient values of 0.81 and 0.87 respectively. Data analysis was done using Pearson Product Moment Correlation with the help of Statistical Package for Social Science (SPSS) version 26. The result of the study showed that there was a statistically significant relationship between student personnel management, financial management and principals’ administrative effectiveness. Based on this, it was concluded that Education Management Information System (EMIS) have a statistically significant relationship with principals’ administrative effectiveness in secondary schools in Ikom Education zone, Cross River State, Nigeria. The study recommended among others that training sessions such seminars and workshop should be organized for secondary school administrators on the utilization of Management Information System to enhance their administrative effectiveness.